Assessment of community livelihood vulnerability to climate change in Vietnam: A case study of ethnic groups in Northern Upland Region - Bui Thi Hoang Lan; Dinh Duc Truong; Tran Tho Dat; Bui Huy Quang; Nguyen Dieu Hang; Le Huy Huan (PLoS ONE, 2025)
This study aims to assess the livelihood vulnerability to climate change of ethnic minority communities in Yen Bai province, a typical mountainous region in northern Vietnam. Utilizing the Livelihood Vulnerability Index (LVI) framework developed by Hahn et al. (2009), in combination with the IPCC vulnerability structure, the research analyzes eight components related to household characteristics, health, food, water, housing and productive land, social and financial networks, livelihood strategies, and exposure to climate shocks. Data were collected through a combination of desk study and survey with 480 households from two major ethnic groups: Tay and Thai.The results indicate that the Thai group has a higher overall LVI score (0.43) compared to the Tay group (0.37), reflecting greater livelihood vulnerability. The main factors contributing to this difference are limited livelihood diversification, lower educational attainment, weaker access to healthcare, and higher dependency on climate-sensitive resources. Although both groups are highly exposed to climate-related hazards such as flash floods, landslides, and droughts, the Thai group demonstrates greater sensitivity and lower adaptive capacity. This research contributes theoretically by adapting and refining the LVI framework to suit the context of upland ethnic communities, and practically by providing empirical evidence to inform climate adaptation policies. The study highlights the need for differentiated and context-specific strategies that prioritize ethnic minority communities with high vulnerability, focusing on improving education, livelihood diversification, healthcare access, and institutional support mechanisms.